Optimization analysis of initial support for tunnels in water-rich fault zone based on fluid-solid interaction - Yuanyuan LI; Chunpeng LI; Dazhao HE; Xin KANG (Shuiwen dizhi gongcheng dizhi)
The design of tunnel support structures in water-rich fault zones often relies on empirical and analogy-based methods, lacking rigorous and rational optimization methods. To ensure the stability of tunnel, designers frequently overestimate support parameters, resulting in excessive safety margins, construction challenges, and unnecessary economic costs. Based on the fluid-structure coupling theory, this study simulated the whole process of tunnel excavation and support across F8 water-rich fault zone by FLAC3D in the background of Longnan tunnel of Ganzhou−Shenzhen railway. Combined with the engineering and hydrogeological conditions of the fault zone and the construction characteristics of the six CD methods, the center axis, left vault area, and right vault area of the middle part of the fault zone were selected to establish the deviation square sum function (ST). The results show that the reasonable space of steel arch frame is 1.0 m, and the recommended shotcrete thickness ranges from 26 to 30 cm, with 28 cm being optimal based on cubic curve fitting. When the space between steel arch frames is 1.0 m, the volume of the plastic zone decreases with the increase of the thickness of the initial branch of shotcrete. However, beyond 28 cm, the marginal benefit diminishes significantly, making further increases uneconomical. To improve the safety of the initial-support structure, and the rationality of the optimization of the spacing of the initial-support steel arch frame and the thickness of shotcrete is verified. Under the optimal initial support condition, the primary seepage pathways are ordered as follows: arch foot > side wall > arch bottom > Arch crown. Comparison between simulated and field-monitored results reveals consistent trends and similar magnitudes, indicating that the simulation accurately reflects actual field behavior. This study provides the theoretical basis for tunnel construction and support design in similar water-rich fault zones.